CURRENT STATE AND PROSPECTS OF UKRAINIAN BAKING INDUSTRY DEVELOPMENT - Д. В. Завертаний (Ринкова економіка: сучасна теорія і практика управління, 2016)
The transformation processes taking place in the Ukrainian economy show the necessitate of the innovative approaches formation at baking enterprises. To improve the efficiency, enterprises in baking industry should not only optimize transport and energy costs, but also develop an effective pricing strategy for finished products. It should be noted that there is a need to run modern technological production lines that will make possible to reduce the prime cost of the finished product. Despite the fact that the baking industry is one of the most dynamic and investment attractive sectors of the food industry in Ukraine, many companies can not compete and therefore lose their market share. They do not invest in the modernization and upgrading of the equipment. In modern scientific literature there is no comprehensive approach in solving problems of the baking industry, improvement of the state policy regulation and the intensification of industrial bakeries in depressed regions. Also, it should be noted that till today any issues on improving the efficiency of bakeries at regional level and ways of increasing the efficiency of production of bread and bakery products in the new market conditions aren’t disclosed. The current state of the baking industry in Ukraine has been analyzed in the article. The main factors causing the reduction of production of baking industry enterprises are: cost, technical, demographic, ethno-cultural, structural and consumer. Also, the article highlights the prospects of the future development of the industry. The analysis contains the data from 2005 to January-October 2015. The overcoming of the crisis in the baking industry and its further development depends on the overcoming of key refraining factors mentioned in the article. Since, baking industry has great political and social importance, manufacturers of bakery products, have to timely evaluate their pricing policy. In turn, government regulation holds back the establishment of new prices, so it significantly limits the freedom of action of the baking industry enterprises.